SUGARCANE CROPS WITH CONTROLLED WATER DEFICIT IN THE SUB- MIDDLE SAO FRANCISCO VALLEY, BRAZIL - Simoes, Welson Lima; Calgaro, Marcelo; Machado Guimaraes, Miguel Julio; Oliveira, Anderson Ramos de; Medeiros Andre Pinheiro, Mirian Paula [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2018)
Sugarcane is one of the most affected crops by water scarcity. The efficient use of the irrigation water is an alternative to minimize this problem. The objective of this work was to evaluate biometric parameters, yield, and technological quality of sugarcane plants subjected to different controlled water deficit regimes in the sub-middle Sao Francisco Valley, Brazil. The experiment was conducted in a randomized block design, in two crop cycles, with three replications, with ten treatments consisted of three controlled water deficits (15%, 30%, and 45% of the crop evapotranspiration - ETc), applied at three development stages of the plant-sprouting and tillering (Stage I), grand growth (Stage II), and maturation (Stage III)-and a control with 100% of the ETc throughout the entire crop cycle. The controlled water deficit did not affect the technological quality of the sugarcane in any development stage. The sugarcane yield was higher when using a controlled water deficit of 30% of ETc in the sprouting and tillering stages of the plants. The water deficit of 15% of ETc is recommended for the grand growth, or maturation stages of the sugarcane plants for a greater water use efficiency of the production system.
Keywords: Saccharum officinarum L.; Irrigation management; Technological quality; Water use efficiency